2021
DOI: 10.3389/fonc.2021.684713
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT Imaging, Biodistribution and Radiation Dosimetry of a 177Lu-DOTA-Integrin αvβ6 Cystine Knot Peptide in a Pancreatic Cancer Xenograft Model

Abstract: IntroductionPancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignant neoplasms, as many cases go undetected until they reach an advanced stage. Integrin αvβ6 is a cell surface receptor overexpressed in PDAC. Consequently, it may serve as a target for the development of probes for imaging diagnosis and radioligand therapy. Engineered cystine knottin peptides specific for integrin αvβ6 have recently been developed showing high affinity and stability. This study aimed to evaluate an integri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…All radiotracers were radiolabeled in good radiochemical purity at a molar activity of 10-18.5 MBq/nmol. A high temperature of 90 • C was required for the labeling, which is consistent with previous studies, which used up to 99 • C for 68 Ga and 80-95 • C for 177 Lu labelings [35][36][37]. In vitro cell-based studies in BxPC-3 cell lines indicated that about 11% internalized for the [ 68 Ga]Ga-DOTA-(PEG28) 2 -A20FMDV2 at 1 h, while the albumin binding constructs had about 8-10%.…”
Section: Discussionsupporting
confidence: 85%
“…All radiotracers were radiolabeled in good radiochemical purity at a molar activity of 10-18.5 MBq/nmol. A high temperature of 90 • C was required for the labeling, which is consistent with previous studies, which used up to 99 • C for 68 Ga and 80-95 • C for 177 Lu labelings [35][36][37]. In vitro cell-based studies in BxPC-3 cell lines indicated that about 11% internalized for the [ 68 Ga]Ga-DOTA-(PEG28) 2 -A20FMDV2 at 1 h, while the albumin binding constructs had about 8-10%.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, α v β 6 -binding cystine knot peptides such as R 0 1 and S 0 2 were developed and optimized, which were first applied for imaging studies in animal models after being radiolabeled with radionuclides. ,, Kimura et al engineered cystine knot peptides R 0 1 mutants, and R 0 1-MG was selected for imaging human α v β 6 -positive cancers, including pancreatic cancer, cervical cancer, and lung cancer . Sachindra et al synthesized 177 Lu-DOTA-R 0 1-MG and performed SPECT/CT imaging, biodistribution, and radiation dosimetry studies . In addition, Tummers et al developed an intraoperative near-infrared fluorescence agent based on R 0 1-MG, which showed specific targeting to α v β 6 in a mouse model of pancreatic cancer .…”
Section: Discussionmentioning
confidence: 91%
“…To preliminary estimate the affinity of the probes for integrin αvβ6, IC 50 values were determined in a competitive binding assay using pancreatic cancer BxPC-3 cells (known to possess a high expression of integrin αvβ6) 32 and not considering the non-specific binding of the peptide ( i.e. with no controls to account for non-specific binding).…”
Section: Resultsmentioning
confidence: 99%